Phase I/II Trial of Immunotherapy with Durvalumab and Tremelimumab With Continuous or Intermittent MEK Inhibitor Selumetinib in NSCLC: Early trial report - Gaudreau, Pierre-Olivier (Clin Lung Cancer, 2020)
Current strategies to improve clinical outcomes in KRAS-mutant non-small cell lung cancer (NSCLC) patients include MEK inhibitor and PD-1 / PD-L1 immune checkpoint blockade (ICB) combinations. Experience from melanoma suggests that anti-CTLA-4 and anti-PD-1 / PD-L1 combinations improve outcomes, but similar benefits remain to be seen in NSCLC. This report describes a single center, investigator-initiated Phase I/II clinical trial comparing two combination schedules of intermittent or continuous selumetinib (AZD6244, ARRY-142886), tremelimumab (anti-CTLA-4) and durvalumab (anti-PD-L1) with historical controls in patients with previously treated, unresectable NSCLC. Forty patients will be accrued at the University of Texas MD Anderson Cancer Center. Primary objectives include maximum tolerated dose (MTD; dose-escalation phase) and Progression-Free Survival (PFS; dose expansion phase). Secondary objectives include response rate by RECIST 1.1, disease control rate, overall survival, safety and duration of response. Exploratory objectives will assess biomarkers of response and resistance based on pre-and on-treatment biopsies and peripheral blood using immune profiling, transcriptome and protein readouts. MICRO ABSTRACT: This investigator-initiated trial was designed to provide novel data regarding: 1) the safety of durvalumab, tremelimumab and selumetinib combination therapy; 2) whether this combination can improve PFS in metastatic NSCLC; 3) potential biomarkers of response and resistance based on pre-and on-treatment biopsies and peripheral blood.